Reinforcing knowledge, market-based incentives, and bean quality in Honduras: estimating impacts of a bundled innovation using a cluster randomized controlled trial - Reyes, Byron A.; Colindres, Mirian; Espada, Andres; Ceballos, Federico; Rodríguez, Carlos; Wiegel, Jennifer Rebecca (2023)
Common beans (Phaseolus vulgaris L.) are an important source of food and protein in Honduras and the region. Smallholders produce most of the beans, and they face many biotic and abiotic challenges. Roughly 10-15% of bean producers in Honduras belong to a farmer association. These associations provide goods and services (technical assistance, inputs, credit, market information) to farmers, expecting members to sell high-quality beans back. However, the associations face challenges to meet their commitments in terms of volume and quality, which also limits their access to better markets, as associated farmers still produce low-quality beans and sell only a share of their harvest to the association. To alleviate these two issues, we are evaluating two innovations that could contribute to increasing grain quality and the share of high-quality beans members sell to their associations, while reducing associations’ processing costs. This poster summarizes results of the baseline survey implemented in the context of this evaluation.